Asthmatic Exacerbation as a Cause of False-Positive Whole-Body Iodine Scan in a Patient With Treated Papillary Thyroid Carcinoma. (April 2018) - Chaussé, Guillaume; Kader, Tina; Abikhzer, Gad; Probst, Stephan
Abstract : Abstract: A 44-year-old woman was found to have new diffuse lung uptake on a follow-up whole-body 131 I scan 1 year after being treated with surgery and radioactive iodine for papillary thyroid cancer. However, subsequent CT thorax and thyroglobulin levels were both unremarkable. Shortly after, she presented with respiratory symptoms, exhibiting end-expiratory wheezing on auscultation. Metacholine challenge test confirmed asthma. Symptoms improved under inhaled corticosteroids and beta-2 agonists. Resolution of lung uptake was confirmed on a second 131 I imaging 6 months later.